Individual-Level Consistency of Different Laterality Measures in the Goldbelly Topminnow. - Dadda, Marco; Nepomnyashchikh, Valentin A.; Izvekov, Evgeny I.; Bisazza, Angelo (Behavioral Neuroscience, 2012)
In humans, hemispheric language dominance is, to some degree, associated with handedness. Significant associations have been reported between several other lateralized functions. Much less is known about the organization of cerebral asymmetries in nonhuman species and, in particular, whether the presence of reversed asymmetry of one function is associated with a reversal of other lateralized functions or, instead, if cognitive functions lateralize independently. In this study, we compare four measures of sensory and motor laterality in the same individuals in a sample of goldbelly topminnows. A significant association was found between two measures of eye preference and two measures of motor laterality, but sensory and motor asymmetries were uncorrected. We found interesting that individuals preferring to examine a predator with the right eye tended to use the left eye to look at a shoal mate and the reverse was true for fish that monitored predators with the left eye. This complementarity of functions could be adaptively advantageous for a small social fish, because it allows an individual to monitor the movements of its shoal mates with one eye as the other eye remains free to scan the surroundings for the presence of predators.